Helping patients help themselves: Supporting the healthcare journey. Issue 9 (September 2018) - Ellen, Moriah E.; Shach, Ruth; Balicer, Ran D.
Abstract: Patients often feel lost when navigating the health care system, and poor care coordination leads to negative patient outcomes, consumes resources and makes diseases more difficult to treat. Patients and citizens have become eager to take health care decision making into their own hands. To this end, solutions have been proposed which assist patients by providing them with more information and enabling them to take a more active role in their care. These include enlisting a patient navigator, consumer engagement, process mapping, decision aids, and clinical pathways. However, as the global penetration of mobile devices approaches 100%, it is timely to update and optimize health system support technologies and information dissemination pathways. There is much room for improvement and health systems are beginning to echo other industries in asking "what do consumers want?" in their applications. We believe that now is the time to address emergent gaps and supplement the irreplaceable human elements of patient navigation with a mobile or computer application. It would be able to automate parts of the process, and consolidate important information, to serve as a broad-reaching, real-time companion for healthcare consumers and their families to accompany them on their journey from diagnosis to follow up.